The Denotative and Connotative Meanings in the Song Lyric of “If Ain’t Got You” By Alicia Keys - Putri Adelia Ningsih Boimau; Yuliyanto Sabat; Siti Aisyah (Universitas Pahlawan Tuanku Tambusai, 2026)
Song lyrics often convey meanings that extend beyond their literal interpretations, making semantic analysis essential for understanding the messages embedded in musical texts. However, studies specifically examining denotative and connotative meanings in English popular songs remain relatively limited. Therefore, this study aims to identify the denotative and connotative meanings found in Alicia Keys' *If I Ain't Got You* and explain how these meanings contribute to the song's overall message. This research employed a descriptive qualitative approach using document analysis as the primary method. The data consisted of lyrical expressions selected from the song and analyzed based on semantic theory. The findings revealed 20 lyrical expressions, including 7 denotative meanings and 13 connotative meanings. The predominance of connotative meanings indicates that figurative and implied language plays a significant role in communicating the song's central message. The analysis shows that the lyrics emphasize the importance of genuine love, emotional connection, and personal fulfillment over material wealth, social status, fame, and power. These findings highlight the value of semantic analysis in revealing deeper meanings and enhancing the interpretation of song lyrics.